2020
DOI: 10.3390/ijerph17207373
|View full text |Cite
|
Sign up to set email alerts
|

Does Masticatory Ability Contribute to Nutritional Status in Older Individuals?

Abstract: Mastication plays a primary role in the process of eating. Hence, compromised masticatory ability may affect the nutrition and quality of life, which are particularly important concerns among older individuals. It remains unclear how is the masticatory ability assessed regarding the nutritional status. We examined the effect of various oral factors on three masticatory ability tests conducted among older individuals. A total of 100 older individuals were enrolled in this study. Body mass index (BMI) as an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Masticatory dysfunction refers to a debilitating condition in which normal masticatory function is compromised by functional factors (e.g., poor masticatory performance) or structural factors (e.g., tooth loss). Studies have reported that the prevalence of masticatory dysfunction in the elderly is 20.3-56.9% (4)(5)(6). Masticatory dysfunction can significantly reduce the nutrient intake levels of older people, except for carbohydrate intake (7).…”
Section: Introductionmentioning
confidence: 99%
“…Masticatory dysfunction refers to a debilitating condition in which normal masticatory function is compromised by functional factors (e.g., poor masticatory performance) or structural factors (e.g., tooth loss). Studies have reported that the prevalence of masticatory dysfunction in the elderly is 20.3-56.9% (4)(5)(6). Masticatory dysfunction can significantly reduce the nutrient intake levels of older people, except for carbohydrate intake (7).…”
Section: Introductionmentioning
confidence: 99%
“…The function and integrity of the masticatory system have an important impact on a person's quality of life (Fujimoto et al, 2020). Poor health of the masticatory system may be caused by many interrelated factors, including tooth decay, tooth loss, malocclusion, temporomandibular joint dysfunction, and mandibular fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, dental infections and inflammation may be aggravated among older people, resulting in worse oral health and obviously promoting a negative self-assessment of their oral health and OHRQoL. 33 A compromised oral health statuses may also contribute to the frailty process given the associated consequences, such as oral hygiene difficulties, chewing problems and malnourishment, 34,35 and sarcopenia. 36,37 The intercorrelation between these conditions suggests the existence of a complex net evolving frailty, oral health, and OHRQoL in older adults.…”
Section: Discussionmentioning
confidence: 99%